3D steganography hiding of information - Kuznetsov А.А.; Stefanovych, O.O.; Prokopovych-Tkachenko, D.I.; Kuznetsova, K.O. (Radiotekhnika, 2018)
A new direction of technical steganography related to the concealment of information in the process of layer-by-layer creation (cultivation) of a solid-state object using various 3D-printing technologies is investigated. Information data are converted into a digital 3D-model of elementary physical objects that are placed inside this 3D-model of the container product. After printing, a solid object physically contains the hidden information that cannot be deleted or distorted without damaging the container product. In addition, the applied methods do not reduce the operational, aesthetic and any other properties of the finished product. The proposed complex is invariant to the method of layer-by-layer growing, that is, it can be equipped with any peripheral devices of 3D-printing of various manufacturers with any materials and principles of layer-by-layer creation.